HUBUNGAN INDEKS MASSA TUBUH (IMT) DAN RASIO LINGKAR PINGGANG PINGGUL (RLPP) DENGAN KADAR GLUKOSA DARAH PUASA PADA PENDERITA DIABETES MELITUS TIPE II DI PUSKESMAS KEBAYORAN LAMA, JAKARTA SELATAN - Sapang, Mertien; Puili, Darwati; Sitoayu, Laras (Lembaga Penerbitan Unversitas Esa Unggul, 2018)
The prevalence of diabetes mellitus (DM) type 2 was increases globally. DM can be affected by several factors such as poor diet, physical inactivity and obesity. The aims this research are to examine the relationship between body mass index (BMI) and waist-hip ratio (WHR) with fasting blood sugar levels in patients with diabetes mellitus. This study used a quantitative research and cross sectional design with 30 subjects. Analysis of data was carried out using pearson correlation. The result of this research showed that almost respondents between 50-64 years old (73.3%) and (83.3%) with low educational (53.3%). The average of WHR are 0.9 and BMI are 27.4 kg/m2. The results showed that BMI have significat association with fasting blood sugar levels (p<0.05). However, there was no significant association between WHR and fasting blood sugar levels. Keywords : diabetes mellitus, body mass index, waist hip ratio